BUKU INTERAKTIF SEBAGAI MEDIA KAMPANYE MANFAAT BROTOWALI BAGI KESEHATAN MASYARAKAT DI KOTA PALEMBANG - Riski Ridwan, Kgs Ahmad; Halim, Bobby; Mubarat, Husni (VisArt: Jurnal Seni Rupa dan Design, 2023)
Abstract: This research based on data from the Palembang City HealthOffice, 27,475 men and 34,000 women affected by diabetes in 2021. This data shows an increase in diabetes so that it can be formulated in this design is how efforts to reduce of diabetes by consuming Brotowali, especially for adolescents in the city of Palembang. Consuming and processing Brotowali is designed interactive books with interesting illustrations and interactives and teaches reading while playing. This study uses the AISAS design method for data collection and data analysis through the 5W + 2H method so as to produce an idea that can be applied at the test stage for adolescents in Palembang and with questionnaire and interview techniques. Respondents in this study were 101 people. The works created are categorized into three media, the main media interactive books, media issues, posters, brochures, xbanners, motion graphics and supporting media, t-shirts, tumblers, stickers, key chains, pencil boxes, wall clocks, totebags, mascots, standing pouches, packaging. This design uses Brotowali illustrations which have characteristic thorny stems and love-shaped leaves, so that teenagers in the city of Palembang are more interested in consuming and processing Brotowali.